Fabrication and characterization of B (Pb)SCCO superconducting whisker Josephson junction - Chaiyachate P. (2014)
We propose a novel method of Josephson junction using Superconducting Whisker B(Pb)SCCO. The B(Pb)SCCO Whiskers were employed in this project were grown by melted-quench method. They were of the form of micro single crystal and shape of ribbons having the dimensions of 10-60 μm x 1-5 μm x 1-5 mm in width, thickness and length, respectively. A pair of Josephson junction could be fabricated by crossing a pair of whiskers and annealing them in O2 flowing atmosphere of 600-800°C for 1 hr. The whiskers then were separated to form independent sets of Josephson junction. Electrical connections to the ends of each whisker were done with silver paste. Josephson Effect of SNS or bridge junction and SIS junction was observed for junction fabricated at 700°C and 750-800°C, respectively. The I-V characteristic of a SNS junction was also studies in the temperature range of 20-90 K by means of a closed circuit cryogenic system. The critical current and critical voltage was increased as the temperature of the junction decreased. At the temperature of 20 K the critical current and critical voltage were 66 μA and 6.5 μV, respectively. In conclusions, Josephson junction SNS and SIS types were successfully fabricated employing B(Pb)SCCO whiskers.